Seismic Performance Evaluation of Stone Masonry Houses Constructed with Reinforced Concrete Bands - Maharjan, Anju; Parajuli, Hari Ram (Nepal Journal of Science and Technology, 2020)
The research work was aimed evaluating the newly built stone masonry houses with mud mortar and with the provision of horizontal reinforced concrete (R.C.) bands. Two recently built stone masonry houses of different geometry were selected, modeled, and analyzed to investigate the seismic performance of stone masonry houses constructed with horizontal bands. Linear time history analysis was used and performance of the selected buildings was checked with the help of various numerical models. The top roof displacement, maximum drift ratio, base shear, and shell stress were compared between two selected models using three earthquake time histories. The fragility curves were also developed to identify the probability of the failure of the buildings at different peak acceleration values using three earthquake time histories.